Perancangan dan Evaluasi UI/UX Aplikasi Perpustakaan Digital Menggunakan Metode Design Thinking dan System Usability Scale - Muhammad Patria; Steven Juan Felix Sihombing; Ilham Setiawan (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Digital libraries play an important role in improving information accessibility and supporting digital literacy. However, many digital library applications still face usability challenges, particularly in navigation, collection retrieval, and digital reading experiences. In addition, previous studies have often focused on either interface design or usability evaluation separately, resulting in limited integration between user-centered design and usability assessment. This study aims to design and evaluate a digital library application by integrating Design Thinking and the System Usability Scale (SUS). The Design Thinking approach was implemented through five stages: empathize, define, ideate, prototype, and test, to identify user needs and develop a clickable prototype using Figma. Usability evaluation was conducted with ten respondents using the SUS instrument. The proposed prototype includes key features such as book search, category-based catalogs, digital reading, and an administrative dashboard. The evaluation produced a SUS score of 77.75, indicating a good level of usability and positive user perception. This study contributes by integrating Design Thinking and SUS within a unified development process to create a user-centered and quantitatively validated digital library prototype.